Innovative Education: Integrating Artificial Intelligent Animation in English in the Implementation of the Independent Curriculum at SMAN Banyuwangi - Muhamad Alfi Khoiruman; Doni Hadi Irawan (ANFA MEDIATAMA, 2023)
The implementation of the Independent Curriculum in Indonesia creates a learning environment that is dynamic and responsive to technological developments. The research aims to improve the quality of English learning at SMAN Banyuwangi through the integration of Artificial Intelligence (AI) animations. By utilizing this innovative technology, it is hoped that it can create a more interesting and effective learning experience for students. This research applies descriptive qualitative methods. Data sources involve the Deputy Principal, teachers and students, with data collection through interviews, observations and analysis of related documents. Interviews provide direct views, observations understand daily practices, and document analysis supports understanding of the Merdeka Curriculum policy. Qualitative analysis uses a thematic analysis approach to identify patterns, themes and relationships from interview data, observations and documents. The results show increased material absorption, leveraging an innovative AI animation approach to improve understanding of difficult concepts visually and increase student engagement, creating a dynamic and collaborative learning environment. Overall, the integration of AI technology, especially English animation, makes a significant contribution to the learning experience at SMAN Banyuwan.